Atmospheric Bridge Connecting the Barents Sea Ice and Snow Depth in the Mid-West Tibetan Plateau - Chen, Yuhang; Duan, Anmin; Li, Dongliang (Frontiers in Earth Science, 2020)
In contrast to the rapid warming of the climate, there is growing evidence to indicate that no significant trend exists in the snow cover/depth over the western Tibetan Plateau in recent decades. Here, by analyzing multiple sources of observational and reanalysis data, we address the possible interannual connection between the mid-west Tibetan Plateau (MWTP) snow depth and Arctic sea ice. Results indicate that a robust and coherent variation exists between the winter Barents Sea ice concentration and the MWTP snow depth; that is, a positive anomaly of the former can enhance the meridional air temperature gradient to the south and hence accelerate the polar-front westerly jet. As a result, an anomalous Rossby wave propagating upwards and equatorwards generates, resulting in a dipole pattern of the atmospheric circulation anomaly over the polar region and the Eurasian continent. The anticyclonic circulation anomaly, corresponding to the south center of the dipole pattern, weakens the subtropical westerly jet and forms a southeast wind climbing the MWTP, which enhances the zonal advection and meridional convergence of the atmospheric moisture flux over the MWTP, and hence facilitates the MWTP snowfall. The interannual variation of the Barents Sea ice and the MWTP snow depth are therefore closely connected through the atmospheric bridge effect of the westerly jet and Rossby wave.